RESPONSE TO STANDARD INTERFERON A2b AND RIBAVIRIN COMBINATION THERAPY IN CHRONIC HEPATITIS C TREATMENT NAÃVE PATIENTS - Jadoon, Shah Muhammad Khan; Jadoon, Samina; Muhammad, Iqbal (Journal of Ayub Medical College Abbottabad, 2010)
Background: Treatment of Chronic Hepatitis C is now well established with conventional interferon or pegylated interferon in combination with ribavirin. Peginterferon Alfa and Ribavirin for 6 to 12 months is currently approved initial therapy, which is expensive. Response of our patients to standard Interferon-alpha-2b and ribavirin for 24 weeks have been studied. The objective of this study was to asses Sustained Viral Response (SVR) with standard Interferon A2b and Ribavirin combination treatment in chronic Hepatitis C patients. Methods: This quasi-experimental study was conducted at Combined Military Hospital, Quetta from Jan 2006 to Jun 2007. One hundred and three patients, with 20-60 years of age suffering from chronic Hepatitis C were selected on the basis of raised ALT, positive anti-HCV antibodies, evidence of viraemia by quantitative PCR for HCV RNA and liver biopsy. All patients were started on same brand of Interferon alpha-2b, 3 MIU subcutaneously, thrice weekly and oral Ribavirin (1,000-1,200 mg/day) for 24 weeks. End treatment response (ETR) after completion of treatment and SVR six months after ETR were recorded. Results: The 103 patients, 85 males and 18 females with mean age of 21-48 years completed the treatment for 24 weeks. Mean ALT was 96.17 (SD±49.98). End treatment response (ETR) was 89.3% (p=0.032). Sustained Viral Response after 6 months of treatment was 86.4% (p=0.034). Conclusion: Standard Interferon and Ribavirin had excellent SVR. It is effective as well as economical treatment in Chronic Hepatitis C patients. Keywords: Chronic Hepatitis C, Interferon A2b, Ribavirin, SVR